Determinación de fosfatasa alcalina como diagnóstico presuntivo en la osteomalacia, pacientes de 30-50 años recinto potosí parroquia Ricaurte cantón Urdaneta primer semestre 2015 - Diego, Carrrera Carrera (2015)
This research in determining alkaline phosphatase as osteomalacia presumptive diagnosis in patients 30-50 years Ricaurte Parish Complex Potosi Canton Urdaneta first half 2015 is performed in order to raise awareness of how determined the levels of alkaline phosphatase us induces a presumptive diagnosis of a bone disease called osteomalacia is known for its effects caused pain to the bones and which prevents the proper operation. Among the objectives of the research is the determination of alkaline phosphatase in the presumptive diagnosis as osteomalacia, establish their incidence in patients aged 30-50. The methodology was based on the collection of bibliographic information I provide sustenance to the theoretical framework. Was evaluated by direct interview patients 30-50 years to evaluate variables in our research were: sex, age, medical history (liver disease, gallstones and heart disease) and medication use and will influence the same elevation they were discarded. This study was conducted in 97 patients aged 30-50 Potosi Campus by clinical history provided by the physician liver, bile and heart problems was discarded. With female predominance of 66% and 34% in males. Therefore this process after research raised a proposal is aimed Strategic Training Plan Aimed at patients 30-50 years will help to reduce the incidence of osteomalacia Complex Potosi.